Respuesta :
When the bases are the same, you can combine the exponents.
x³ [x is where the base is]
For example:
x³ · y² = x³y² You can't simplify this anymore because they have different bases/variables
[when you multiply a variable with an exponent by a variable with an exponent, you add the exponents together] so:
x² · x³ = [tex]x^{2+3}=x^5[/tex]
[when you multiply a variable with an exponent by an exponent, you multiply the exponents together] so:
(x³)²=[tex]x^{3*2}=x^6[/tex]
[tex]-2y^2*xy^4=-2x(y^{2+4})=-2xy^6[/tex]
Answer:
[tex]\large\boxed{-2xy^6}[/tex]
Step-by-step explanation:
[tex]-2y^2\cdot xy^4=(-2)(x)(y^2y^4)\\\\\text{use}\ a^na^m=a^{n+m}\\\\=-2xy^{2+4}=-2xy^6[/tex]